A Fully Packed Magnetoelectric VLF Communication System Based on Self-Designed Circuits and Wireless Transmission into a Metallic Enclosure - Zhu, Mingmin; Chen, Yu; Bao, Teng; Chen, Jiajin; Shi, Lingshan; Yu, Guoliang; Li, Yan; Zhu, Haibin; Qiu, Yang; Zhou, Haomiao (IEEE transactions on antennas and propagation, 2023)
Magnetoelectric (ME) antennas have offered significant advantages in the design of very-low-frequency (VLF) communication systems operating in challenging environments such as underground, underwater, and inside metallic enclosures. However, state of the art ME-based communication systems either depend on bulky commercial signal processing instruments or have limited reports on digital signal transmissions. In this work, we demonstrate a compact design of an ME VLF communication system based on self-designed modulator and demodulator circuits, working at the electromechanical resonance frequency of the ME antenna and having a remarkably reduced size for greater applicability in realistic industrial scenarios. The concept of sending Morse code through amplitude-shift-keying modulation was confirmed in the proposed ME VLF communication system. Our findings revealed that the maximum communication distance can be considered as 5.7 m when the bit-error-rate is limited to 10 -2 . Furthermore, VLF wireless signal transfer through a harsh environment (metal box) was verified with our communication system. An effective communication distance of 0.85 m could be realized when placing the ME receiver in a 5 mm iron box, demonstrating the ability of the wireless signal to penetrate conductive media. The proposed fully packed ME VLF communication system provides advantageous alternative for underground, underwater, and inside-metal-containers communications.